2017
DOI: 10.3390/su9040665
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Ecosystem Services in European Cities in the Continental Biogeographical Region in the Period from 1990–2012

Abstract: Ecosystem services (ES) in cities and surrounding suburban areas are one of the major factors which guarantee quality of life. Most studies directly referring to urban ecosystem services are conducted on a local scale or for selected cities. There are few studies which focus on temporal changes of the provision of ecosystem services across a large number of cities. This paper analyzes selected land use type (forest, green urban area), soil sealing, selected ecosystem services (food provisioning, climate regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Currently, owing to the growing demand for mineral resources, the number of degraded and destroyed sites worldwide has increased [7][8][9][10][11], and opencast mining often has irreversible natural consequences. Mineral resource mining has one of the strongest impacts among all industries, distorting the natural environment globally [12,13] and often causing it to lose its ecological functions [14]. The regeneration and reclamation of areas degraded by human activity is conditioned by both social and natural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, owing to the growing demand for mineral resources, the number of degraded and destroyed sites worldwide has increased [7][8][9][10][11], and opencast mining often has irreversible natural consequences. Mineral resource mining has one of the strongest impacts among all industries, distorting the natural environment globally [12,13] and often causing it to lose its ecological functions [14]. The regeneration and reclamation of areas degraded by human activity is conditioned by both social and natural aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of these changes result in the degradation of ESs, which is the aggregate of ecosystem goods (such as food) and services (such as waste assimilation), that represent the benefits human populations derive, directly or indirectly, from ecosystem functions [12]. These impacts make the quantification of Ecosystem Service Values (ESVs) essential to raise awareness [13], develop decision making for the distribution of scarce resources among conflicting demands [14], incorporate ESs into the socioeconomic and marketing systems [15], formulate policy [16] and stimulate the conservation of ecosystems that deliver the most valuable services in support of human well-being [17].Following the pioneering works of Costanza et al [18], who estimated global ESVs by suggesting a list of ESV coefficients for different biomes, the evaluation of ESVs and their changes has received broad attention [15,16,19]. Since then, to support mitigations of local degradation and global change problems, the interest in the valuation of ESs has grown rapidly in research and policy making communities.…”
mentioning
confidence: 99%
“…The consequences of these changes result in the degradation of ESs, which is the aggregate of ecosystem goods (such as food) and services (such as waste assimilation), that represent the benefits human populations derive, directly or indirectly, from ecosystem functions [12]. These impacts make the quantification of Ecosystem Service Values (ESVs) essential to raise awareness [13], develop decision making for the distribution of scarce resources among conflicting demands [14], incorporate ESs into the socioeconomic and marketing systems [15], formulate policy [16] and stimulate the conservation of ecosystems that deliver the most valuable services in support of human well-being [17].…”
mentioning
confidence: 99%
“…Moreover, they concluded that of all land changes, 60% are associated with direct human activities and only 40% with indirect environmental drivers, e.g., climate change. In addition, land cover changes exhibit regional dominance in agricultural intensification, temperate reforestation or afforestation, and urbanization [7,17,19,63].…”
Section: Discussionmentioning
confidence: 99%
“…They cover such processes as urbanization, intensification, and extensification of agriculture, and deforestation and afforestation [15,16]. Particularly noteworthy are studies concerning land cover dynamics and its impact on the environment and economy [16], changes in ecosystems [17,18] and climate [19], hazards and risk assessment [20], water and soil properties [21], urban sprawl [22], and land take [16,23]. In addition, the CORINE land cover technology was successfully transferred to several African countries [24,25].…”
Section: Introductionmentioning
confidence: 99%